THE INFLUENCE OF ENTREPRENEURIAL ORIENTATION, WORK-LIFE BALANCE, AND CAREER CHOICE ON THE ENTREPRENEURIAL INTENTION OF GENERATION Y - Ie, Mei; Rorlen, Rorlen; Buana, Salsabila Ayunda Martsa; Gunawan, Ferdyanto (International Journal of Application on Economics and Business, 2025)
Entrepreneurial intentions in Generation Y are influenced by various factors that reflect their preferences and life orientation. Entrepreneurial orientation will form a proactive mindset and dare to take risks. Work-life balance is also an important consideration for Generation Y who crave flexibility and balance between their personal and work lives. Meanwhile, career choice determines the direction of an individual's decision in choosing the career that best suits their aspirations, including the tendency to become an entrepreneur. Therefore, these three factors are seen as interrelated in influencing the entrepreneurial intention of Generation Y. The purpose of this research is to enrich the literature related to the variables of entrepreneurial orientation, work life balance, and career choice on the entrepreneurial intention of Generation Y. The sample amounted to 100 employee respondents in the age range of generation Y.